Case report: Successful treatment of mediastinal unicentric castleman disease using cardiopulmonary bypass - Ran, Wei; Cuilin, Zhu; Hulin, Piao; Kexiang, Liu (Frontiers in Cardiovascular Medicine, 2023)
Unicentric castleman's disease（UCD）is a rare benign lymphoid tissue proliferative disease. Mediastinal UCD, with no clear boundaries, is highly vascularized. Resection surgery results in bleeding, which is more challenging. And UCD with a mixed pathology is uncommon . We present a 38-year-old asymptomatic case of UCD with a mixed pathology, which is 7.8 cm in size and the boundary is not clear . The mass was successfully resected with the application of cardiopulmonary bypass(CPB) on beating heart and the patient recovered uneventfully.